Increased serum renalase in peritoneal dialysis patients: Is it related to cardiovascular disease risk? - Ebru Gok Oguz; Hadim Akoglu; Gulay Ulusal Okyay; Guner Karaveli Gursoy; Tolga Yildirim; Ozgur Merhametsiz; Tolga Cimen; Basol Canbakan; Ekrem Yeter; M. Deniz Ayli (Nefrología, 2017)
Background: Renalase, with possible monoamine oxidase activity, is implicated in degradation of catecholamines; which suggests novel mechanisms of cardiovascular complications in patients with chronic kidney diseases. Epicardial adipose tissue (EAT) has been found to correlate with cardiovascular diseases (CVD) in dialysis patients. The present study aimed to evaluate the association of serum renalase levels with EAT thickness and other CVD risk factors in peritoneal dialysis (PD) patients. Methods: The study included 40 PD patients and 40 healthy controls. All subjects underwent blood pressure and anthropometric measurements. Serum renalase was assessed by using a commercially available assay. Transthoracic echocardiography was used to measure EAT thickness and left ventricular mass index (LVMI) in all subjects. Results: The median serum renalase level was significantly higher in the PD patients than in the control group [176.5 (100–278.3) vs 122 (53.3–170.0) ng/ml] (p = 0.001). Renalase was positively correlated with C-reactive protein (r = 0.705, p < 0.001) and negatively correlated with RRF (r = −0.511, p = 0.021). No correlation was observed between renalase and EAT thickness or LVMI. There was a strong correlation between EAT thickness and LVMI in both the PD patients and the controls (r = 0.848, p < 0.001 and r = 0.640, p < 0.001 respectively). Conclusions: This study indicates that renalase is associated with CRP and residual renal function but not with EAT thickness as CVD risk factors in PD patients.